Modification of Adomian Decomposition Method Using (AMJ) Transform for Solving Linear and Nonlinear Schrodinger Equationn (Journal of Hama University, 2025)
The aim of this work to to modify the Adomian decomposition method by integrating it with (AMJ) transform to solve partial differential equations, We applied this modification to solve the linear and nonlinear Schrodinger equation with important applications in various physical and engineering fields, We obtained the actual solution to the studied problems for multiple iterations. The results showed the accuracy and effectiveness of this method as it can be used as an alternative method to solve different models of linear or nonlinear  partial differential equations
Keywords: Adomian Decomposition Method; AMJ Transform; linear Schrodinger Equation; Nonlinear Schrodinger Equation; Actual Solution